Dose-Escalation Study of Systemically Delivered rAAVrh74.MHCK7.micro-dystrophin in the mdx Mouse Model of Duchenne Muscular Dystrophy - Potter, Rachael A. (Hum Gene Ther, 2021)
Duchenne muscular dystrophy (DMD) is a rare, X-linked, fatal, degenerative neuromuscular disease caused by mutations in the DMD gene. More than 2,000 mutations of the DMD gene are responsible for progressive loss of muscle strength, loss of ambulation, and generally respiratory and cardiac failure by age 30. Recently, gene transfer therapy has received widespread interest as a disease-modifying treatment for all patients with DMD. We designed an adeno-associated virus vector (rAAVrh74) containing a codon-optimized human micro-dystrophin transgene driven by a skeletal and cardiac muscle-specific promoter, MHCK7. To test the efficacy of rAAVrh74.MHCK7.micro-dystrophin, we evaluated systemic injections in mdx (dystrophin-null) mice at low (2 × 10(12) vector genome [vg] total dose, 8 × 10(13) vg/kg), intermediate (6 × 10(12) vg total dose, 2 × 10(14) vg/kg), and high doses (1.2 × 10(13) vg total dose, 6 × 10(14) vg/kg). Three months posttreatment, specific force increased in the diaphragm (DIA) and tibialis anterior muscle, with intermediate and high doses eliciting force outputs at wild-type (WT) levels. Histological improvement included reductions in fibrosis and normalization of myofiber size, specifically in the DIA, where results for low and intermediate doses were not significantly different from the WT. Significant reduction in central nucleation was also observed, although complete normalization to WT was not seen. No vector-associated toxicity was reported either by clinical or organ-specific laboratory assessments or following formal histopathology. The findings in this preclinical study provided proof of principle for safety and efficacy of systemic delivery of rAAVrh74.MHCK7.micro-dystrophin at high vector titers, supporting initiation of a Phase I/II safety study in boys with DMD.